COMPARISON OF EARLY VERSUS DELAYED INTUBATION OUTCOMES IN PATIENTS WITH SEVERE TRAUMATIC BRAIN INJURY (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Severe traumatic brain injury (TBI) is a major cause of mortality and long-term disability worldwide and represents a significant burden on healthcare systems, particularly in developing countries. Airway compromise, hypoxia, and inadequate ventilation are common in patients with severe TBI and can lead to secondary brain injury, thereby worsening neurological outcomes. Endotracheal intubation is frequently performed in critically ill trauma patients to secure the airway, maintain adequate oxygenation, and facilitate mechanical ventilation. However, the optimal timing of intubation in severe traumatic brain injury remains controversial.Early intubation may prevent hypoxia, aspiration, and hypercapnia while allowing improved airway protection and better physiological stabilization. Conversely, delayed intubation may result in deterioration of neurological status, respiratory compromise, and increased secondary brain injury. On the other hand, unnecessary early intubation may expose patients to procedure-related complications, prolonged mechanical ventilation, ventilator-associated pneumonia, and increased intensive care unit stay. Therefore, evaluating the impact of timing of intubation on clinical outcomes is essential for optimizing critical care management in severe TBI patients.Aim: To compare the outcomes of early versus delayed intubation in patients with severe traumatic brain injury.Objectives• To compare mortality rates between early and delayed intubation groups.• To evaluate neurological outcomes in patients undergoing early versus delayed intubation.• To assess duration of mechanical ventilation, ICU stay, and hospital stay in both groups.• To compare complications associated with early and delayed intubation in severe traumatic brain injury patients.Methodology: This prospective observational study was conducted in the Department of Critical Care at a tertiary care hospital over a period of one year during the period from January 2025 to December 2025. A total of 50 patients aged between 30 and 60 years diagnosed with severe traumatic brain injury were included in the study.Patients were categorized into two groups:• Early intubation group• Delayed intubation groupPatients with severe TBI requiring airway management and intensive care support were enrolled after fulfilling the inclusion and exclusion criteria. Relevant demographic details, clinical presentation, Glasgow Coma Scale (GCS) score, imaging findings, duration of ventilation, ICU stay, hospital stay, complications, and clinical outcomes were recorded and analyzed.Statistical analysis was performed using appropriate descriptive and inferential statistical methods. A p-value less than 0.05 was considered statistically significant.Results: Patients who underwent early intubation demonstrated improved airway stabilization, reduced episodes of hypoxia, shorter ICU stay, and better neurological outcomes compared to patients undergoing delayed intubation. Delayed intubation was associated with increased incidence of respiratory complications, prolonged mechanical ventilation, and higher mortality rates.Early intubation also contributed to improved hemodynamic stabilization and reduced secondary brain injury. However, procedure-related complications and ventilator-associated events were observed in both groups.Conclusion: Early intubation in patients with severe traumatic brain injury was associated with improved clinical outcomes, reduced secondary complications, shorter intensive care stay, and lower mortality compared to delayed intubation. Appropriate airway management and timely intervention remain critical components in the management of severe TBI patients.Early recognition of airway compromise and prompt intubation in selected patients may significantly improve neurological recovery and overall survival outcomes in severe traumatic brain injury.